Forms of Constitutional Disobedience Against Final and Binding Decisions of the Constitutional Court - Hoky Yuro Herlambang (CV. Era Digital Nusantara, 2026)
Abstract: Constitutional Court rulings are final and binding, and thus must be obeyed by all state institutions. Indonesian constitutional practice reveals instances of non-compliance with Constitutional Court rulings—manifested through delayed implementation, disregard for the ruling's operative provisions, or the enactment of new norms that contradict the Court's decisions. This situation gives rise to a phenomenon of